Isospin Effect on fragment productions and reaction mechanisms for Ni+Ca systems at 25 AMeV. (December 2020) - Geraci, E; Cardella, G; Colonna, M; De Filippo, E; Gnoffo, B; Lanzalone, G; Lo Monaco, L; Maiolino, C; Martorana, N S; Pagano, A; Pagano, E V; Papa, M; et al.
Abstract: Main features of fragments produced in 58Ni+40Ca and 58Ni+48Ca systems at 25 AMeV, collected by Chimera multidetector at INFN Laboratori Nazionali del Sud (Italy), are analysed in order to study properties of moderately excited systems (Ex=2-5 AMeV) formed in central collisions. By means of correlations between specific global variables, sensitive to the centrality of the collision, a stringent selection of Fusion-Evaporation residues, Multifragmentation sources and their decay products has been performed. The influence of the isospin contents of the systems on the reaction mechanism is carefully investigated and relevant observables such as isospin asymmetry N/Z or charge and mass of fragments, are discussed in order to probe the fragmentation path, characterised by short living ( ∼ 100fm/c) low density states of nuclear matter out of equilibrium. Preliminary comparisons with predictions of the BLOB model, in a semi-classical mean field framework, are presented, investigating cluster production emerging from the occurrence of low-density instabilities in central collisions.